The effects of photon-upconversion nanoparticles on the growth of radish and duckweed: Bioaccumulation, imaging, and spectroscopic studies - Modlitbová, Pavlína; Hlaváček, Antonín; Švestková, Tereza; Pořízka, Pavel; Šimoníková, Lucie; Novotný, Karel; Kaiser, Jozef (Chemosphere, 2019)
In this study, radish (Raphanus sativus L.) and common duckweed (Lemna minor L.) were treated with an aqueous dispersion of carboxylated silica-coated photon-upconversion nanoparticles containing rare-earth elements (Y, Yb, and Er). The total concentration of rare earths and their bioaccumulation factors were determined in root, hypocotyl, and leaves of R. sativus after 72 h, and in L. minor fronds after 168 h. In R. sativus, translocation factors were determined as the ratio of rare earths concentration in hypocotyl versus root and in leaves versus hypocotyl. The lengths of the root and hypocotyl in R. sativus, as well as the frond area in L. minor, were monitored as toxicity endpoints. To distinguish rare earth bioaccumulation patterns, two-dimensional maps of elemental distribution in the whole R. sativus plant and L. minor fronds were obtained by laser-induced breakdown spectroscopy with a lateral resolution of 100 μm. Moreover, the bioaccumulation was inspected using a photon-upconversion laser microscanner. The results revealed that the tested nanoparticles became adsorbed onto L. minor fronds and R. sativus roots, as well as transferred from roots through the hypocotyl and into leaves of R. sativus. The bioaccumulation patterns and spatial distribution of rare earths in nanoparticle-treated plants therefore differed from those of the positive control. Overall, carboxylated silica-coated photon-upconversion nanoparticles are stable, can easily translocate from roots to leaves, and are expected to become adsorbed onto the plant surface. They are also significantly toxic to the tested plants at nominal concentrations of 100 and 1000 μg/mL.
Keywords: Lemna minor L.; spektrální analýza; Erbium; Spectrum Analysis; Laser-induced breakdown spectroscopy; Photons; Plant Extracts; Raphanus sativus L.; Raphanus; fotony; rostlinné extrakty; Ytterbium; Nanoparticles; Yttrium; nanočástice